(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
Integrated agricultural production systems aim at sustainability, seeking to exploit the maximum of the area, as well as reducing impacts on soil properties. The present study had the objective of studying the distribution of pore size of an Oxisol in an integrated agricultural production system after three years of system implantation. The experiment was carried out at Fazenda belonging to the Facholi group, in the municipality of Caiuá / SP. The experimental design was a randomized complete block with three replicates and composed of 7 treatments: 1 - Soya - Maize + B. ruziziensis (grazing); 2 - Soya - Maize + Piatã (grazing); 3 - Soybean - Maize + Paiaguás (grazing); 4 - Soya - Piatã (grazing 2 years) - Soya - Piatã (grazing); 5 - Soybean - Paiaguás (grazing 2 years) - Soybean - Paiaguás (grazing); 6 - Soybean - corn (Direct planting); 7 - Soybean - corn (Conventional preparation). The following soil attributes were evaluated: macroporosity, microporosity, total porosity and soil bulk density, in two depths of soil; 0.00-0.10 and 0.10-0.20 m depths, in three collection seasons. The results show that the macroporosity increased with time and there was a decrease in the soil bulk density, showing that the evaluated systems influenced positively the soil attributes studied, thus improving soil quality.